Europeanisation of public debate: Swedish And Finnish news on African migration to Spain - Horsti, Karina (Javnost-The Public, 2008)
Immigration is a policy fi eld increasingly shifting under supranational decision-making in the EU. This article analyses news coverage of African “illegal” migration to the Canary Islands in a Finnish and a Swedish newspaper. Analysis of the northern European public debate of a southern European news event shows how the “migration crisis” is simultaneously Europeanised and domesticated in Finland, yet treated as a typical foreign news event in Sweden. Domestication increases coverage and viewpoints: in addition to the dominating news frames which present the African migrants as objects of criminalisation, control, and victimisation, reportage from Africa suggests a heroic frame. Although there are characteristics of a mediatised public crisis within the event, and therefore potential for social change through increased media salience, the main news coverage remains stigmatising – constructing a division between Europe and Africa.